Biological Databases: ’IT’ Revolutionising Data Management Systems in Molecular Biology - Dasharathy, Radhika (Journal of Information and Knowledge, 2002)
The advancement in the field of information technology is gradually revolutionizing the tradltlonal expenmental methods and interpretations made in classical biology research. The results are such that, even vital fields like the Pharmaceuticals are influenced by Bioinformatics (Biology with Infonnation Technology). Powerful tools right from storing a sequence (DNA/protein) to analysing and interpreting results are available today. This inturn is bound to reduce the research gestation period and also enhance the accuracy of the results obtained. One of the main reasons for this is the availability of efficient computational tools and relational database management system (RDBMS).